PENERAPAN STRATEGI PEMBELAJARAN AKTIF FORMASI REGU TEMBAK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI IPA SMA NEGERI 10 PEKANBARU - Oktariani, Diny; Herdini, Herdini; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is about the application of active learning the firing line strategy that has conducted to know the increasing of student’s learning achievement on chemical equilibrium topic in class XI IPA in 10 Senior High School Pekanbaru. This research was experiment by design pretest and posttest. The sample determined randomly after doing normality and homogeneity test of 5 classes as population and then class XI IPA 5 as experiment class and XI IPA 4 as class group. The experiment group was applied by the application of active learning the firing line strategy. The data analysis technique used was t - test. Based on the tabulation of last data obtained tcount>ttable was 2,36 ≥ 1,67 meant that the application of active learning the firing line strategy could increase the student’s learning achievement on Solubility and Constanta Solubility Product topic in class XI IPA in 10 Senior High School Pekanbaru. Category increase the student’s learning achievement trhough active learning the firing line strategy on the subject of chemical equilibrium is a high category of 0,77.Keywords: The Firing Line, Active Learning, Achievement, Chemical Equilibirium